Training on the Folklore Nasi Menangis as a Form of Oral Tradition Appreciation, Food Waste Mitigation, and Mindful Eating Habituation for the Parents of Students at SD Negeri 01 Ngijo, Semarang - Muzakki Bashori; Wasino Wasino; Meddiati Fajri Putri; Inez Kalyana Azmi; Abdul Rozaq; Herlina Putri Khawismaya; Rahma Danisa Eka Safitri (Jurnal Penelitian Pendidikan, 2024)
This community service program aims to conduct storytelling training on the folklore "Nasi Menangis" as a means to enhance appreciation for oral traditions, reduce food waste, and foster the habit of mindful eating among students of SD Negeri 01 Ngijo, Semarang. The Nasi Menangis folklore conveys moral messages about respecting food and the importance of minimizing food waste. Through a series of training activities, parents of the students are encouraged to understand and appreciate the rich local culture embedded in the folklore. Additionally, they gain insights into the significance of mitigating food waste to support environmental sustainability. This program also introduces the concept of mindful eating practicing full awareness while eating to help students develop healthier and more sustainable eating habits. The implementation of the program involves collaboration between the school, educators, parents, and students. An evaluation process measures the program’s impact on the parents’ efforts to improve students' understanding of oral traditions, food waste mitigation, and mindful eating habits. It is hoped that this program will not only provide educational benefits to the students but also encourage the preservation of local culture, reduce food waste, and shape a generation more conscious of the importance of environmental sustainability and health through wise eating practices.